FRI0090 Analysis of neutrophils, lymphocytes, and platelets in pooled phase 2 and phase 3 studies of baricitinib for rheumatoid arthritis. (15th June 2017) - Kremer, J; Huizinga, TWJ; Chen, L; Saifan, CG; Issa, M; Witt, SL; Walls, CD; Torre, I de la
Abstract : Background: Rheumatoid arthritis (RA) is associated with increased neutrophil levels 1 and platelet 2 counts and decreased lymphocyte levels. 1, 3 Baricitinib (bari) is a selective and reversible Janus kinase (JAK)1/JAK2 inhibitor in development for patients (pts) with moderate to severe RA. 4 Objectives: To characterize changes in absolute neutrophil counts (ANC), absolute leukocyte counts (ALC), and platelet counts following once daily oral administration of bari. Methods: Data were pooled from 6 placebo-controlled phase 2 and 3 studies of bari (2 and 4 mg). Changes in ANC, ALC, and platelets were evaluated for up to 52 weeks (wks) including data from a long-term extension study. Reversibility was evaluated in a subgroup of pts who discontinued treatment by wk 24. Results: Mean ANC decreased within 1 month of administration of bari, followed by stabilization and an increase to baseline after treatment discontinuation (Figure 1 ). ANC <1000 cells/mm 3 were reported in <1% of pts, and 2 bari-treated pts (0.1%) reported permanent discontinuation of study drug due to neutropenia. Incidence of neutropenia was not associated with higher risk of overall or serious infections (Table 1 ). Mean ALC increased within 1 month of bari administration and then decreased to baseline level in wks 12 to 24 (Figure 1 ). Lymphopenia appeared to be associated with slightly higher rate of overall infections (Table 1 ). Mean platelet counts increased to peak at wk 2, returned towards baseline, stabilized over time, and returned to baseline after treatment discontinuation (Figure 1 ). Permanent study drug discontinuations from thrombocytosis occurred in 2 bari-treated pts (0.1%). No clear association between platelet increase and thromboembolic events was observed. Conclusions: Treatment with bari was associated with a decrease in ANC and an increase in ALC and platelets, which stabilized over time and returned to baseline with prolonged treatment (ALC) or treatment discontinuation (ANC and platelets). No associations between ANC decrease and infections or between thrombocytosis and thromboembolic events were observed. References: Schulze-Koops H et al. Rheumatology. 2017;56(1):46–57. Farr M et al. Ann Rheum Dis. 1983;42(5):545–549. Symmons DP et al. J R Soc Med. 1989;82:462–463. Fridman JS et al. J Immunol. 2010;184:5298–5307. Disclosure of Interest: J. Kremer Grant/research support from: Abbvie, Genentech, Eli Lilly and Company, Novartis, Pfizer, Consultant for: Abbvie, Amgen, BMS, Genentech, GSK, Eli Lilly and Company, Novartis, Pfizer, Employee of: Corrona, Speakers bureau: Genentech (non-promotional), T. W. J. Huizinga Grant/research support from: Eli Lilly and Company, Pfizer, Consultant for: Eli Lilly and Company, Pfizer, Speakers bureau: Eli Lilly and Company, Pfizer, L. Chen Employee of: Eli Lilly and Company, C. Saifan Employee of: Eli Lilly and Company, M. Issa Employee of: Eli Lilly and Company, S. Witt Employee of: Eli Lilly and Company, C. Walls Employee of: Eli Lilly and Company, I. de la Torre Employee of: Eli Lilly and Company